Treatment sequence of synchronously (liver) metastasized colon cancer. Issue 10 (October 2016) - Gruenberger, Thomas; Beets, Geerard; Van Laethem, Jean-Luc; Rougier, Philippe; Cervantes, Andrés; Douillard, Jean-Yves; Figueras, Joan; Gruenberger, Birgit; Haller, Daniel G.; Labianca, Roberto; Maleux, Geert; Roth, Arnaud; et al.
Abstract: No standards for staging, systemic therapy or the timing of an operation are defined for patients newly diagnosed with synchronous metastases and a primary in the colon. An expert group of radiologists, medical, radiation and surgical oncologists therefore came together to discuss staging and treatment sequence for these patients and came up with a recommendation based on current evidence of potential therapeutic options. The discussion was organized to debate recommendations centred on 5 topics and therefore the position paper is built upon these titles and their subtitles.